Protective effects of Ganoderma lucidum spores on estradiol benzoate-induced TEC apoptosis and compromised double-positive thymocyte development - Yang, Jihong; Pan, Haitao; Wang, Mengyao; Li, Anyao; Zhang, Guoliang; Fan, Xiaohui; Li, Zhenhao (Frontiers in Pharmacology, 2024)
Backgroud: Thymic atrophy marks the onset of immune aging, precipitating developmental anomalies in T cells. Numerous clinical and preclinical investigations have underscored the regulatory role of Ganoderma lucidum spores (GLS) in T cell development. However, the precise mechanisms underlying this regulation remain elusive.In this study, a mice model of estradiol benzoate (EB)-induced thymic atrophy was constructed, and the improvement effect of GLS on thymic atrophy was evaluated. Then, we employs multi-omics techniques to elucidate how GLS modulates T cell development amidst EB-induced thymic atrophy in mice.Results: GLS effectively mitigates EB-induced thymic damage by attenuating apoptotic thymic epithelial cells (TECs) and enhancing the output of CD4 + T cells into peripheral blood. During thymic T cell development, sporoderm-removed GLS (RGLS) promotes T cell receptor (TCR) α rearrangement by augmenting V-J fragment rearrangement frequency and efficiency. Notably, biased Vα14-Jα18 rearrangement fosters double-positive (DP) to invariant natural killer T (iNKT) cell differentiation, partially contingent on RGLS-mediated restriction of peptide-major histocompatibility complex I (pMHCⅠ)-CD8 interaction and augmented CD1d expression in DP thymocytes, thereby promoting DP to CD4 + iNKT cell development. Furthermore, RGLS amplifies interaction between a DP subpopulation, termed DPsel-7, and plasmacytoid dendritic cells (pDCs), likely facilitating the subsequent development of double-negative iNKT1 cells. Lastly, RGLS suppresses EB-induced up-regulation of Abpob and Apoa4, curbing the clearance of CD4 + Abpob + and CD4 + Apoa4 + T cells by mTECs, resulting in enhanced CD4 + T cell output.Discussion: These findings indicate that the RGLS effectively mitigates EB-induced TEC apoptosis and compromised double-positive thymocyte development. These insights into RGLS's immunoregulatory role pave the way for its potential as a T-cell regeneration inducer.